Do Farmers Choose to Be Inefficient? Evidence from Bicol - Larson, Donald F.; Plessmann, Frank (2012)
Farming households that differ in their ability or willingness to take on risks are likely to allocate resources and effort among income producing activities differently with consequences for productivity. In this paper we measure voluntary and involuntary departures from efficiency for rice producing households in the Bicol region of the Philippines. We take advantage of a panel of observations on households from 1978, 1983 and 1994. Available monthly weather data and survey information on planting times allows us to create household specific measures of weather shocks, which we use in our analysis. We find evidence that diversification and input choices do affect efficiency outcomes among farmers, although these effects are not dominant; accumulated wealth, past decisions to invest, favorable market conditions, and propitious weather are also important determinants of efficiency outcomes among Bicol rice farmers. Our findings suggest that the costs of incomplete formal and informal insurance markets are higher for poorer farmers.